1996
DOI: 10.1021/jm960537g
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosides and Nucleotides. 158. 1-(3-C-Ethynyl-β-d-ribo-pentofuranosyl)- cytosine, 1-(3-C-Ethynyl-β-d-ribo-pentofuranosyl)uracil, and Their Nucleobase Analogues as New Potential Multifunctional Antitumor Nucleosides with a Broad Spectrum of Activity

Abstract: We previously designed 1-(3-C-ethynyl-beta-D-ribo-pentofuranosyl)uracil (EUrd) as a potential multifunctional antitumor nucleoside antimetabolite. It showed a potent and broad spectrum of antitumor activity against various human tumor cells in vitro and in vivo. To determine the structure-activity relationship, various nucleobase analogues of EUrd, such as 5-fluorouracil, thymine, cytosine, 5-fluorocytosine, adenine, and guanine derivatives, were synthesized by condensation of 1-O-acetyl-2,3,5-tri-O-benzoyl-3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
117
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 127 publications
(118 citation statements)
references
References 25 publications
0
117
0
1
Order By: Relevance
“…1-(3-C-ethynyl-b-D-ribo-pentofuranosyl)cytosine (TAS106) was synthesised as described elsewhere (Hattori et al, 1996). Ultrapure nitrogen gas (99.999%) was obtained from Air Water Technical Supply (Ishikari, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1-(3-C-ethynyl-b-D-ribo-pentofuranosyl)cytosine (TAS106) was synthesised as described elsewhere (Hattori et al, 1996). Ultrapure nitrogen gas (99.999%) was obtained from Air Water Technical Supply (Ishikari, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of its inhibitory effect on RNA polymerase, TAS106 is known to regulate the expression of its target proteins at the transcriptional level (Maehara et al, 1982;Hattori et al, 1996;Matsuda and Sasaki, 2004). In this study, we examined the effect of TAS106 on the mRNA expression of HIF-1a using semiquantitative RT -PCR.…”
Section: Hif-1a Downregulation By Tas106 Is Largely Dependent On Tranmentioning
confidence: 99%
See 1 more Smart Citation
“…1) is a new cytidine analogue showing significant cytotoxicity and antitumor activity in preclinical therapeutic models. [1][2][3] The results of several studies show that TAS-106 acts by interfering with RNA metabolism.2, 4-7) Further in vitro studies on RNA polymerase II, an enzyme expressed in the nuclear extracts from HeLa cells, revealed that the triphosphate of TAS-106, ECTP, inhibited in a concentration-dependent manner the activity of that enzyme.4) The action of TAS-106 on RNA polymerase-specific transcription was demonstrated to be without specificity for RNA polymerase I, II or III in K562 human leukemia cells.5) Moreover, in preliminary experiments, RNA polymerase was inhibited competitively by ECTP with a K i value of 21 nM (apparent K m value of CTP, 8.0 µM) in isolated nuclei of FM3A mouse mammary tumor cells.6, 7) ECTP was found to accumulate as the major intracellular metabolite following the exposure of the cells to TAS-106 for 4 h and was then very slowly eliminated from the cells.5, 6) Therefore, intracellular accumulation and retention of the active metabolite ECTP may contribute to the potent cytotoxicity of TAS-106. This profile, considered to reflect a unique mechanism of antitumor activity and cellular metabolism, makes TAS-106 different from other antitumor nucleosides and TAS-106 is a promising candidate as a therapeutic agent for cancer patients.…”
mentioning
confidence: 99%
“…1) is a new cytidine analogue showing significant cytotoxicity and antitumor activity in preclinical therapeutic models. [1][2][3] The results of several studies show that TAS-106 acts by interfering with RNA metabolism.…”
mentioning
confidence: 99%